From formulations to functionality: tannic acid crosslinked gelatine as extended-release hydrophilic matrices for buccal delivery / Amina Ahmady - Ahmady, Amina (2024)
Gelatine, a biopolymer known for its rapid dissolution at physiological temperature and limited mucoadhesive properties, is suboptimal as a mucoadhesive polymer for buccal film formulations with an extended mode of action. This study aimed to evaluate the potential of the gelatine films cross-linked with tannic acid (GelTA) as mucoadhesive matrices for extended buccal drug delivery. Initially, blank GelTA films were prepared using the solvent evaporation technique and evaluated for their mechanical, mucoadhesive, and dissolution characteristics. The key formulation variables included gelatine source (bovine and fish), tannic acid concentrations, the pH of the film-forming solutions, and the type and concentration of plasticisers. In the second stage, a subset of films was further analysed, exploring their antimicrobial and antioxidant properties and evaluating their stability under varying storage conditions. The final research stage focused on the evaluation of GelTA films as carriers for the model drug, cetylpyridinium chloride (CPC). After determining the solubility of CPC in selected GelTA films, they were loaded with 20% and 40% w/w CPC and subjected to comprehensive characterisation. The results demonstrated a significant enhancement in the dissolution time of GelTA films compared to non-crosslinked gelatine films, while maintaining their water-absorbing capacity. In particular, BG-TA5-GLY20-71 exhibited a 1.6-fold increase in mucoadhesivity compared to its non-crosslinked counterpart (BG-GLY202). Additionally, blank GelTA films exhibited superior antioxidant properties compared to BG-GLY20. The solubility of CPC in GelTA films containing 2% and 5% tannic acid increased by 2 and 3 times, respectively, compared to BG-GLY20. GelTA films exhibited extended CPC release over 360 min, unlike BGGLY20 which released CPC in less than 120 min. Based on drug release data, BG-TA2GLY20-7 loaded with 40% w/w CPC effectively achieved the required concentration to inhibit four targeted microorganisms: C. albicans, S. mutans, S. aureus, and SARS CoV2. Additionally, GelTA films exhibited zero-order drug release kinetics and CPC release occurred through erosion. Regarding retention time on chicken pouch mucosa, BG-TA5-GLY20-7 and BG-TA2-GLY20-73 outperformed BG-TA2-GLY20-84 In particular, CPC did not permeate significantly through chicken pouch mucosa membranes, supporting the suitability of these films for topical drug delivery systems. In conclusion, GelTA films prepared at pH 7 exhibited superior characteristics for extended intraoral CPC delivery, considering the CPC release profile, erodibility, and adhesion times. However, stability studies indicate the need for an oxygen-free environment during GelTA film storage.